ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s)
Gas tankers sction; President Samuel Kanyon Doe's arrival from a conference in Ivory coast; assembly of Health Ministers (West Africa); second half match (Bundesliga) between Hamburg and Vfl Leverkusen.
Keywords: Sports; News